ANALISIS PENGARUH KUALITAS PELAYANAN SUB BAGIAN AKADEMIK TERHADAP KEPUASAN MAHASISWA DI FAKULTAS KEDOKTERAN UNIVERSITAS DIPONEGORO SEMARANG - Triyani, Dian; Sarbina, Dyah ayu belawanti; Prapti N.S.S, Lulus (Fakultas Ekonomi, Universitas Semarang, 2021)
This study aims to determine the quality of academic service on student satisfaction. The object of this research at the Faculty of Medicine, Diponegoro University. The independent variables in this study are tangibles, responsiveness, reliability, empathy and assurance. The dependent variable in this study is student satisfaction at the Faculty of Medicine at Diponegoro University.The population in this research is 4522 active students with a sample of 97 students. The method used in this research is a probability sampling method with proportional stratified random sampling technique. This research uses Multiple Linear Regression Analysis tool.The results showed that the tangibles, responsiveness, reliability and empathy partially has a positive and significant effect on student satisfaction. Assurance variable doesn t have effect on student satisfaction at the Faculty of Medicine, University Diponegoro.